PEMISAHAN Zr – Hf SECARA SINAMBUNG MENGGUNAKAN MIXER SETTLER - Biyantoro, Dwi; Isyuniarto; Masrukan (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
Separation of Zr - Hf continuously using mixer settler 16 stage has been done. The feed solution is zircon nitrate concentration of Zr = 30786 ppm and Hf = 499 ppm. As the solvent used extractant 60 % TBP in 40 % kerosene. Nitric acid solution used srubbing 1 M. The feed entered into stage to 5 is contacted with solvents direction on the stage to 16 and the scrubbing solution enter the stage to 1. The purpose of this study is to separate Zr and Hf of the results from the process of zircon sand using solvent TBP using 16 stage mixer settlers. Analysis of the feed and the results of the separation process for zirconium (Zr) using X-ray fluorescence instrument which hafnium (Hf) using Neutron Activation Analysis (AAN). Parameter study done of acidity variation of nitric acid in the feed and time variation in various stirring speed. From the research the separation of Zr-Hf, the optimum conditions in acidity feed 4 N HNO3, equilibrium was received after 3 hours, and stirring speed of 3300 rpm obtained extract of zircon (Zr) concentration = 28577 ppm (efficiency of Zr = 92,76 %) with impurities of hafnium (Hf) = 95 ppm.